Antibacterial activity of ionic liquids based on betalactamantibiotics against resistant bacteria - Dias, Vitorino (2019)
The cases of antibiotic resistance are increasing and becoming more and more common, giving rise to a new problem for public health. Therefore, the discovery of new antibiotics is important and necessary.